Bilateral Anterior and Posterior Lens Dislocation in Marfan Syndrome in Teenager : A Case Report: Poster Presentation - Case Report - General practitioner - Daeli, Pasti Rahmat; Ferdiansyah, Muhammad; Agustiawan, Referano; Ihsan, Nasheul (Majalah Oftalmologi Indonesia, 2023)
Introduction : The zonular defect leads to ectopia lentis, which is a hallmark of Marfan ocular abnormalities. Bilateral dislocation of lens in marfan’s syndrome occurs frequently in same location. In this case the lens of RE dislocated in the anterior chamber and the lens of LE was found in vitreous cavity. Iris fixation IOL and Yamane’s scleral fixation technique are prompt treatment for crystalline lens displacement. Case Illustration : A 14 year-old male patient came with chief complaint a painless blurred vision on LE since 2 weeks before visit Ophthalmologist. The BCVA in both eyes was 6/30 RE and 1/60 LE. There was no history of ocular injury nor development disorder. Lens dislocation in anterior chamber was found in RE and aphakic lens was found in LE during slit lamp examination. The IOP ODS were 9.7 mmHg and 3.0 mmHg. Further examination from funduscopy showed the lens of LE was seen in vitreous cavity. Discussion : Bilateral dislocation of lens in opposite position are quite rare. To avoid many of the potential complications, Iris Fixation IOL placement is preferred choice to improve visual impairment on the right eye. Yamane’s Scleral Fixation technique has been performed on left eye however challenging and time consuming it is, to achieve excellent improvement with minimal or no intra- and postoperative complications. Conclusion : This case shows that manifest of crystalline lens in marfan syndrome could happen differently to each eye. Different surgical approach especially IOL placement technique is crucial and must be considered carefully depends on the condition during surgery.